Magnetohydrodynamics (MHD) radiated nanomaterial viscous material flow by a curved surface with second order slip and entropy generation. (June 2020) - Muhammad, Riaz; Khan, M. Ijaz; Khan, Niaz B.; Jameel, Mohammed
Highlights: Magnetohydrodynamics flow of viscous fluid is considered over a curved surface. Buongiorno model is used in the mathematical modeling of flow problem. Total entropy is calculated through second law of thermodynamics. Homogeneous-heterogeneous reactions are considered at the stretchable surface. Abstract: Background: Magnetohydrodynamics or hydro-magnetics (MHD) is the study of dynamics in the presence of magnetic characteristics and impact of electrically conducting liquids which has a significant applications in engineering and biomedical sciences. Liquid metals, plasma, electrolytes and salt water are the examples of such magneto-fluids. MHD liquid flow in various geometries significant to engineering sciences is an interesting and noteworthy scientific area because of applications. The above applications of magnetohydrodynamics insist the engineers and analyst to develop new mathematical modeling in the field of fluid mechanics. Therefore, we considered electrical conducting viscous fluid flow over a curved surface with second order slip. The Buongiorno model is utilized in the modeling of flow problem with thermophoretic and Brownian diffusions. The effects of viscous dissipation, thermal radiation and Joule heating (Ohmic heating) is used in the modeling of energy equation. Homogeneous-heterogeneous reactions are further considered. The energy equation is modeled. Method: The nonlinear ODE's are obtained through utilization of appropriate transformations and numerical results are computed via NDSolve MATHEMATICA. Results: Velocity field is decreasing function of first order slip parameter. Both Bejan number and entropy generation is upsurged versus heterogeneous reaction parameter.